Case of an Exotic Skin and Soft Tissue Infection Associated with Cyclone Ockhi. Issue 1 (June 2021) - Sivadasan, Sreekumar; Reghukumar, Aravind; Gurudas, Athul; V. Sasidharan, Kiran Kumar; Nair, Sruti P.
Vibrio vulnificus is a halophilic marine gram-negative bacillus that is known to cause fulminant primary septicemia and complicated skin and soft tissue infections in humans. Vibrio vulnificus is referred to as flesh-eating bacteria. In the absence of timely detection and treatment, it results in sepsis with mortality of 50% and septic shock with mortality as high as 100%. Primary septicemia occurs following ingestion of contaminated seafood, and wound infections are acquired following exposure of open wounds to contaminated seawater. Early clinical suspicion and initiation of the appropriate antibiotics is essential to ensure good clinical outcome in case of Vibrio vulnificus septicemia. Here we report the case of a fisherman injured in cyclone Ockhi admitted to our hospital with lower limb cellulitis, who was diagnosed as Vibrio vulnificus wound infection. This case emphasizes the importance of history and clinical examination in antibiotic stewardship.